Mechanisms of the Reaction between Polyhalogenated Nitrobutadienes and Electron-Deficient Anilines: Computational Modeling - ERDEM, SAFİYE (AMER CHEMICAL SOC, 2014)
Nitro-substituted polyhalogenated butadienes are valuable synthetic precursors for polyfunctionalized bioactive heterocyclic compounds. Recently, a new reaction between 2-nitroperchloro-1,3-butadiene and electron-deficient anilines producing the Z stereoisomers of a variety of allylidene arylhydrazines has been reported. Although the formation of a chlorinated nitrile oxide intermediate was proved by trapping it with appropriate alkenes via 1,3-dipolar cycloaddition, the details of the overall mechanism remained unclear. The elucidation of the mechanism is important for a better understanding of polyhalogenated nitrobutadiene chemistry. We proposed six reaction paths for the formation of allylidene arylhydrazine, starting from 2-nitroperchloro-1,3-butadiene and para-nitro aniline, and generated the potential energy profiles with the DFT/B3LYP/6-31+G(d,p) method. To include the solvent effect, single-point energy calculations were carried out at the B3LYP/6-31+G(d,p) level by the polarizable continuum model with tetrahydrofuran, as used in the experimental study. The Gibbs activation energies of the rate-determining steps of each mechanism were defined. Taking into account the downhill nature of the overall potential energy profile, Paths 5 and 6 which proceed via extrusion of p-nitrophenylisocyanate and the formation of chlorinated nitrile oxide were chosen as plausible mechanisms. Results also provide insights into the chemistry of nitrile oxides, oximes, oxazete, and nitroso compounds as well as S(N)Vin reactions.
Keywords: STEREOELECTRONIC CONTROL; AB-INITIO; CHEMISTRY; NITROENAMINES; DERIVATIVES; ACCESS; DFT